2020
DOI: 10.1177/1532673x20961024
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics and Partisanship: Following Old Paths into Uncharted Territory

Abstract: Although partisan politics tend be set aside during crisis, the timing of gubernatorial actions in response to COVID-19 is telling about how partisanship is shaping the way elected officials are reacting to this pandemic. Using an event history analysis, the authors find that Democratic governors responded to the White House’s attempts to downplay the severity of the pandemic by declaring emergencies in order to draw citizen attention to and to prepare for a public health crisis. On the other hand, Republican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…Declaring a state of emergency empowers governors to take extraordinary measures to protect public health and safety, such as stay-at-home orders. Fowler et al (2021) developed an event history model in which the dependent variable is the date the emergency was declared; they control for other variables such as the proportion of the population over age sixty and population density, both of which are related to higher mortality and morbidity. They found that “Democratic governors were about 2.67 times quicker to declare a state of emergency than Republican governors, which largely conforms to our expectations of a partisan gap in responses to the pandemic” ( Fowler et al 2021 , 9).…”
Section: The Gap Between Promise and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Declaring a state of emergency empowers governors to take extraordinary measures to protect public health and safety, such as stay-at-home orders. Fowler et al (2021) developed an event history model in which the dependent variable is the date the emergency was declared; they control for other variables such as the proportion of the population over age sixty and population density, both of which are related to higher mortality and morbidity. They found that “Democratic governors were about 2.67 times quicker to declare a state of emergency than Republican governors, which largely conforms to our expectations of a partisan gap in responses to the pandemic” ( Fowler et al 2021 , 9).…”
Section: The Gap Between Promise and Performancementioning
confidence: 99%
“… Fowler et al (2021) developed an event history model in which the dependent variable is the date the emergency was declared; they control for other variables such as the proportion of the population over age sixty and population density, both of which are related to higher mortality and morbidity. They found that “Democratic governors were about 2.67 times quicker to declare a state of emergency than Republican governors, which largely conforms to our expectations of a partisan gap in responses to the pandemic” ( Fowler et al 2021 , 9). They also found that Republican governors were quicker to adopt emergency declarations in states where Trump was less popular, which suggests that these governors responded to the specific political climate in their states.…”
Section: The Gap Between Promise and Performancementioning
confidence: 99%
“…Underlying these dynamics is that federalism has served as a battleground for partisan warfare in recent years, which is part of a larger pattern of divergent policies across states. Specific to COVID-19, Democratic governors asserted their power, at least partially, as a political strategy to challenge the Trump White House, while Republican governors were wary of breaking from party doctrine set by the President (Goelzhauser and Rose 2017;Daguerre and Conlan 2020;Kettl 2020;Kincaid and Leckrone 2020;Fowler, Kettler, and Witt 2021).…”
mentioning
confidence: 99%
“…U.S. state public health responses to the pandemic have also differed based on partisanship. Democratic governors moved more quickly to make emergency declarations related to COVID-19 than did Republican governors ( Fowler et al, 2020 ). Thus, if COVID-19 beliefs and behaviors are observed to organize according to political ideology, it makes sense that partisan communication resources would be important in COVID-19 communication ecologies.…”
Section: Discussionmentioning
confidence: 99%